Pengembangan Ruang Hijau Berbasis Partisipasi Masyarakat di Kelurahan Pahandut Seberang Kota Palangka Raya - Syahrozi; Noor Hamidah; Dwi Anung Nindito; Mahdi Santoso (Fakultas Teknik Universitas Palangka Raya, 2025)
The potential of mothers' groups in processing routine activities, both religious and social deepening activities. The PDPPM FT UPR team initiated a service collaboration with the mothers in RT.03/RW.02, especially the guardians of students at the Ar Raudah Muslimat NU Kindergarten, Pahandut Seberang Subdistrict, in utilizing their yards for vegetable planting activities. Mothers, guardians of Ar Raudah Muslimat NU Kindergarten students, Pahandut Seberang Subdistrict routinely take the children to school. The aim of the service team's activities is to identify activities that can be carried out by mothers, such as using the yard to grow fruit and vegetables. Fruit and vegetables function to fulfill food security for the family. The method uses qualitative methods through observation and interviews for the implementation of service starting from the stage of selecting fruit and vegetable seeds, planting to maintaining the plants. The location of the service is planned in a residential area near the center of worship, namely TK Ar Raudah Muslimat NU Pahandut Seberang. The activity phase began with mediation of service ideas or discussion forums with student mothers at Ar Raudah Muslimat NU Kindergarten, Pahandut Seberang Subdistrict as partners directed by the Head of RT.03/RW.02. The service stage determines the service location for implementing the creative green concept, namely fruit and vegetables, the implementation stage carries out outreach related to the application of the green space concept. The socialization stage is followed by training starting from measuring the land, marking and plotting the yard for planting plants and maintaining vegetables and fruit. Implementation of the Community Empowerment Assistant Lecturer Program by the Faculty of Engineering team, Palangka Raya University in partnership with a group of mothers in utilizing limited land in the yard for fruit and vegetable plants